Oral hygiene practices and their influence on the oral health of adolescents - Shenoy, Rekha P.; Salam T. A., Abdul; Agrawal, Reema; Shenoy K., Prashanth (International Journal Of Community Medicine And Public Health, 2020)
Background: Oral diseases are major public health problems due to their high prevalence and significant social impact. Oral hygiene practices play a critical role in their prevention and control. This study was carried out to evaluate oral hygiene practices and oral status among adolescents in Mangalore taluk, taking into account differences based on location and type of school. Methods: A descriptive cross-sectional study was carried out among 1340 students enrolled in public and private high schools in urban and rural areas of Mangalore taluk. The study sample was equally distributed among urban and rural areas, and among public and private schools. Proforma was prepared to record demographic data, oral hygiene practices, dental caries and periodontal disease. Data were analyzed using Chi-squared test and t-test, with p<0.05 considered statistically significant. Results: Majority of the students used toothbrush and toothpaste to clean their teeth. Horizontal tooth brushing motion and once/twice daily tooth brushing frequency was reported by the highest number of students. Good oral hygiene was found among 55.2% participants. Female participants, urban children and those attending private schools presented with better oral hygiene. Prevalence of dental caries was 59.2%. Prevalence of gingivitis was 83.2%, with higher prevalence among females and rural participants. Poor oral hygiene was found to be associated with gingivitis (r=0.59). Conclusions: Although majority of the participants reported use of requisite oral hygiene aids and regular tooth brushing habits, the high prevalence of oral disease among them can be attributed to poor oral hygiene.